Is West Sumatera local regulation number 6 year 2020 creating compliant community behavior using masks as a preventive effort for Covid-19 in Padang City? - Putri, Z.A. Prima (BKM Public Health and Community Medicine, 2021)
Objective: This study was conducted to explain the compliance behavior of the community using masks in Padang city after Local Regulation Number 6 Year 2020 Passed. Method: Qualitative studies were conducted by in-depth interviews with community and public health experts, observation, as well as literature study related journals. Result: Based on the theory of TRA and TPB found factors namely the behavioral intention not to using masks due to the encouragement of attitudes toward behavior, subjective norms, and perceived behavioral control. Attitudes towards the behavior of not using masks are influenced by the formation of false stigma caused by misinformation or believing conspiracy theories. The subjective norm is obtained from the experience when people often do not use masks while out of the house turns out that no sanctions are obtained. It is like being an unwritten agreement of themselves that there is no regulation so binding on the compliance of using a mask. Perception of behavior control that has knowledge and ability to behave using masks but intentions and awareness that does not exist yet. This is due to the belief to control such behavior is low, because people are not used to wearing masks before, indolent, uncomfortable, hard to breathe, do not have the mask itself, and assume that pain is destiny. Conclusion: The policy to control Covid-19 with Local Regulation Number 6 Year 2020 has not been fully influenced people’s behavior. There is still a need for improvement related to the socialization, monitoring and evaluation carried out. Therefore, a reactive attitude from the government, empowerment and community engagement are required. Such as government collaboration with health NGOs, community leaders, and volunteers.